Molecular evidence on the systematic position of the lance-headed pitviper Protobothrops maolanensis Yang et al., 2011 - Liu, Qin; Myers, Edward A.; Zhong, Guang H.; Hu, Jian; Zhao, Hui; Guo, Peng (Zootaxa, 2012)
In order to assess the phylogenetic position of the recently described Protobothrops maolanensis Yang et al., 2011, wereconstructed relationships within the genus Protobothrops based on four mtDNA gene fragments (12S RNA, 16S RNA,ND4 and cyt b). Phylogeny reconstruction consistently recovered a sister relationship between P. maolanensis and P. ele-gans though with uncompelling support. However, a clade composed of P. maolanensis, P. mucrosquamatus and P. ele-gans was recovered with strong support. The genetic distance between P. maolanensis and P. elegans and between P.maolanensis and P. mucrosquamatus is relatively high compared to other sister-species comparisons within sampled Pro-tobothrops. Given the molecular results and morphological differences, we conclude that P. maolanensis is a valid species closely related to P. elegans and P. mucrosquamatus.